INTEGRASI ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) DALAM PENGUKURAN KINERJA KEBERLANJUTAN PERUSAHAAN - Rosa Fitriana; Nenden Hendayani (JEBIMAN : Jurnal Ekonomi, Bisnis, Managemen dan Akuntansi, 2026)
This study examines the integration of Environmental, Social, and Governance (ESG) in measuring corporate sustainability performance through a systematic literature review approach with two main discussions, namely the theoretical concept of ESG integration and the challenges and benefits of its implementation in the context of Indonesian companies. The results of the study found that ESG revolutionises performance evaluation from purely financial metrics to a holistic approach that mitigates climate, social, and governance risks while creating long-term value through operational efficiency, green financing, and global competitiveness. Although challenges such as Scope 3 data limitations, high compliance costs, and greenwashing risk are dominant in SMEs and state-owned enterprises, the benefits of reduced cost of capital, ROI from carbon markets, and polycrisis resilience outweigh the obstacles, with recommendations for a national digital platform and human resource training to accelerate the transition towards the Indonesia Emas 2045 vision